Airbnb and the housing market in the covid-19 pandemic: A comparative study of Barcelona and Lisbon - Garha, Nachatter S. (2022)
Since 2010, Airbnb has had a significant impact on the housing market in all tourist cities where it operates. With a very small investment, Airbnb enables the use of residential flats for short-term rentals, creating a rent increase that ulti- mately excludes long-term tenants. Using data drawn from the Inside Airbnb website, Idealista, and the 2011 Census of Spain and Portugal, this article first estimates the number of commercial listings, multi-hosts, and long-term rentals lost to Airbnb in Barcelona and Lisbon; second, it measures the potential increase in rents created by Airbnb in specific neigh- bourhoods in both cities; and finally, it examines the impact of the covid-19 pandemic on Airbnb activity in these cities.